A dual quasi-zero-stiffness sliding-mode triboelectric nanogenerator for harvesting ultralow-low frequency vibration energy. (April 2021) - Wang, Kai; Zhou, Jiaxi; Ouyang, Huajiang; Chang, Yaopeng; Xu, Daolin
Abstract: A major purpose of energy harvesting from ambient vibration is to power sensors for structural health monitoring and environment monitoring. However, most types of ambient vibration are in the low-frequency region, which would make conventional energy harvesters inefficient. In this paper, the first attempt to combine a quasi-zero-stiffness (QZS) mechanism and a triboelectric nanogenerator is made, and a QZS triboelectric nanogenerator (QZS-TENG) is devised. In this QZS system, a negative stiffness mechanism (NSM) is constructed by using QZS springs to achieve ultra-low stiffness in a much larger displacement region than that of a traditional QZS device. Based on the geometrical relationship, the exact expression of the restoring force of the QZS-TENG is derived firstly, and then is fitted as a polynomial to obtain its approximate analytical dynamic responses. The electrical properties of the QZS-TENG, including its open circuit voltage, short circuit current, output voltage, output current and output power, are presented in both analytical and numerical results. The numerical results show excellent agreement with the analytical ones, and most importantly, the QZS-TENG exhibits an excellent energy harvesting performance in the ultralow frequency region. This work provides a new application of a QZS mechanism to harvest the ultralow-frequency vibration energy by combining a TENG.